Delayed Response (Partial Remission) 3 Years After Peptide Receptor Radionuclide Therapy in a Patient Participating in the NETTER-1 Trial. (March 2019) - Zhang, Jingjing; Kulkarni, Harshad R.; Singh, Aviral; Baum, Richard P.
Abstract : Abstract: Peptide receptor radionuclide therapy (PRRT) with radiolabeled somatostatin analogues has been shown to be highly efficacious concerning progression-free survival and response rates in patients with advanced, progressive, well-differentiated, somatostatin-receptor–positive neuroendocrine neoplasm. We report here delayed response of a midgut neuroendocrine neoplasm patient, who had stable disease after 4 cycles of PRRT and over a long period of 5 restaging admissions with excellent quality of life (full working hours), persisting for 3 years of follow-up, and presented as further partial remission according to both Response Evaluation Criteria in Solid Tumors and EORTC criteria, respectively, 36 months after the last PRRT cycle.